Agile by design : an implementation guide to analytic lifecycle management - Alt-Simmons, Rachel, 1971- (Hoboken, New Jersey : Wiley, 2016)
Beyond merely defining analytics projects, this important book equips you with the information you need to apply agile methodologies in a way that tailors your approach to individual initiatives{OCLCbr#97}and the needs of your projects and team. --
Adjusting to a Customer-Centric Landscape -- The Analytic Lifecycle -- Getting Your Analytic Project off the Ground -- Project Justification and Prioritization -- Analytics : the Agile Way -- Analytic Planning Hierarchies -- Our Analytic Scrum Framework -- Analytic Scrum Roles and Responsibilities -- Gathering Analytic User Stories -- Facilitating Your Story Workshop -- Collecting Knowledge Through Spikes -- Shaping the Analytic Product Backlog -- The Analytic Sprint : Planning and Execution -- The Analytic Sprint : Review and Retrospective -- Building in Quality and Simplicity -- Collaboration and Communication -- Business Implementation Planning -- Building Agility into Test-and-Learn Strategies -- Operationalizing Your Model Deployment Strategy -- Analytic Ever After.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business planning; Organizational change; Organizational effectiveness; Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Business planning; Management; Organizational change; Organizational effectiveness; Electronic books; Electronic books